Effect of Substrate Temperature on the Structural and Optical Properties of In2O3/InN Nanostructure Composite for Photoelectrochemical Performance. (2018) - Saroni, Azianty; Abdul Rahman, Saadah; Tong Goh, Boon
Abstract: In2 O3 /InN nanostructure composites were grown by nitrogen plasma assisted in-situ thermal annealing at different substrate temperatures, Ts . At Ts = 200 °C a cauliflower like morphology of In2 O3 /InN nanostructure composites with a grain size (∼100-200 nm) were formed. Higher substrate temperature leads to larger grain size (∼400-500 nm). The composite grown at Ts = 200 °C showed a promising In2 O3 /InN with a visible optical band gap of 2.63 eV. This composite exhibited a high photocurrent density response which more than 50 % (equivalent to 795 μA/cm 2 ) upon illumination of visible light compared to the dark condition (< 10 μA/cm 2 ) at 1 VAg/AgCl. Moreover, the formation of In2O3/InN nanostructure composite suppresses the electron/hole recombination leading to the enhancement of the photoelectrochemical processes